HUBUNGAN KONSEP DIRI DAN PERSEPSI POLA ASUH AUTHORITATIVE DENGAN KEMANDIRIAN BELAJAR PADA SISWA - Rifah Marfuati; Triana Noor Edwina Dewayani Suharto (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2019)
This study aims to determine the relationship between self-concept and authoritative parenting perception towards the autonomous learning on the ninth grade students of 1 Yogyakarta State Madrasah Tsanawiyah. To analyze the research data; product moment and multiple regression analysis were conducted.The results of this study indicate that there is a positive relationship between self-concept and the autonomous learning on students of 1 Yogyakarta State Madrasah Tsanawiyah, with a correlation coefficient of 0.551 and p = 0.000 (p<0.05); there is a positive relationship between the authoritative parenting perception and the autonomous learning on students of 1 Yogyakarta State Madrasah Tsanawiyah, with a correlation coefficient of 0.271 and p =Â 0.000 (p<0.05); there is a positive relationship between self-concept and authoritative parenting perception with the autonomous learning on students of 1 Yogyakarta State Madrasah Tsanawiyah, with r value of 0.552 and R square value of 0.404 or 40.4%, meaning that 40.4% of the autonomous learning on students are influenced by self-concept and authoritative parenting perception